Urban Forest Ecosystem Approaches to Mitigating Urban Heat Island Effects - Osu Oheoputra Husen; Hasddin; Alfian Ishak; Ahmad Haeruddin Tiro; Johri Hidayat; De Naddya Yaumil Fadillah Sumarata; Jei Akeo (Jurnal Sylva Lestari, 2026)
The urban heat island phenomenon has become a major concern for medium-sized tropical coastal cities, driven by interactions among land-use change, increasing building density, and the effectiveness of spatial planning. This paper examines how urban forest distribution and building density relate to urban heat island intensity using an urban ecology framework, remote sensing-based spatial analysis, including normalized difference vegetation index (NDVI), normalized difference built-up index (NDBI), and land surface temperature (LST), and spatial planning policy evaluation. The study combines Landsat imagery (2015–2023) with spatial planning documents, green space data, and stakeholder interviews. LST was obtained from NDVI-based emissivity-corrected digital number temperature-radiation-brightness conversion, and linear regression was used to determine the impact of NDVI and NDBI on LST. Based on the research findings, the two cities show different LST patterns. In Baubau, the temperature rise is largely influenced by building density, meaning the denser the buildings, the hotter the city becomes. In Kendari, on the other hand, temperature changes are more strongly influenced by vegetation density. Important ecological features, such as urban forests, mangrove forests, and coastal vegetation, remain scattered along the city’s outskirts. Their existence has not been fully integrated into urban spatial planning. As a follow-up to these findings, we emphasize the need for ecosystem-based measures to tackle the urban heat island effect. This includes tightening regulations on building density and green open spaces through permitting systems, as well as preserving remaining vegetation while developing well-integrated green corridors. Keywords: Baubau, building intensity, green open space, Kendari, land surface temperature, urban ecology